Advances in Safety Management and Human Factors Proceedings of the AHFE 2018 International Conference on Safety Management and Human Factors, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Arezes, Pedro Miguel Ferreira Martins; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses the latest findings on ensuring employees' safety, health, and welfare at work. It combines a range of disciplines - e.g. work physiology, health informatics, safety engineering, workplace design, injury prevention, and occupational psychology - and presents new strategies for safety management, including accident prevention methods such as performance testing and participatory ergonomics. The book, which is based on the AHFE 2018 International Conference on Safety Management and Human Factors, held on July 21-25, 2018, in Orlando, Florida, USA, provides readers, including decision makers, professional ergonomists and program managers in government and public authorities, with a timely snapshot of the state of the art in the field of safety, health, and welfare management. It also addresses agencies such as the Occupational Safety and Health Administration (OSHA) and the National Institute for Occupational Safety and Health (NIOSH), as well as other professionalsdealing with occupational safety and health.
High reliability organisation principles of collective mindfulness: An opportunity to improve construction safety management -- Measure evaluation tool met: Promoting safety by optimizing the human scope of action -- Safety assessment for decommissioning worker -- Development of enterprise accident early warning system based on IOT -- Application fuzzy evaluation methods on safety management of industrial enterprise -- Dynamic analysis of enterprise security system based on multi-level analysis and structural equation model -- Effect of experimental and mathematical modelling of spillway on dam safety -- Safety and risks factors affecting telecommunication mast riggers and technicians in Nigeria -- Risks related to the application of hydrogen propulsion technology in cars -- Analyzing the impact of group norms on workers' safety behaviors in a construction teamInfluential factors of unsafe acts of contractors in cape coast metropolis -- Influential factors of unsafe acts of contractors in cape coast metropolis.
Keywords: Security systems; Occupational health services; Psychology, Industrial; User interfaces (Computer systems).; Human-computer interaction; Engineering design; Security Science and Technology; Occupational Health; Work and Organizational Psychology; User Interfaces and Human Computer Interaction; Engineering Design